Managing challenges in social care service triads – Exploring public procurement practices of Dutch municipalities. Issue 1 (January 2019) - Uenk, Niels; Telgen, Jan
Abstract: Buying services in a triad constellation is associated with challenges related to quality control, performance monitoring, and a deteriorating information position for the buyer. There is growing attention for service triads in Supply Chain Management (SCM) literature. However, these studies are mainly theoretical. The studies suggest to manage the identified challenges by monitoring supplier performance, maintaining a strong position in the service triad, developing collaborative trusting relationships, using outcome-based contracts, and aligning incentives between buyer and suppliers. Empirical studies on service triads and management mechanisms are rare, especially in a public procurement context. We study the application of management mechanisms in a public procurement context where 393 Dutch municipalities each had to contract social care service providers at the same time. This context allows us to study which of the management mechanisms proposed in literature are actually employed in a public procurement context, and whether other mechanisms are applied that are not addressed in the literature. We find municipalities deviate from traditional bureaucratic procurement procedures and apply a relational approach to the procurement procedure, including establishing social contracts, to cope with buyer challenges in service triads. Furthermore we identify municipalities apply ex post competition to drive up service quality through tendering framework agreements and allowing clients to choose their care provider of choice. This mechanism of ex post competition through the use of framework agreements has not been suggested in service triad literature before, and may be an effective mechanism in other service triads to address service quality and customer needs fulfilment issues. Highlights: Public service triads have received little academic attention despite their relevance. We analyse management mechanisms to cope with challenges in service triads. 382 municipalities contracting social care mainly opt for ex post competition. Municipalities mainly choose relational contracting over traditional competitive tendering. This ex post competitive mechanism has not yet been discussed in service triad literature.